Life Cycle Extension of a Pavement Structure - Jan Mikolaj; Lubos Remek; Matus Kozel (Communications - Scientific letters of the University of Zilina, 2016)
The pavement structure, namely pavement surfacing must meet the criteria required to provide operational service during the whole life cycle of the pavement. Surfacing design composed of layer strengths and proposed materials is defined by design method which calculates the stress state during long-term transport and environmental conditions. The designed surfacing life cycle is defined in respect to traffic load acting on the pavement and road class for a period of about 20 years. Given the practical aspects of road administration, pavement reconstruction is usually due only at the end of the life cycle, when the original materials are replaced by new materials and the layer strength is re-evaluated. Since the overall life cycle of the whole pavement is significantly longer than that of the surfacing, it is necessary to consider possibilities to extend the life cycle of the surfacing either through various technologies, i.e. reinforcement, overlays or recycling. Timing of execution of such action plays a paramount role, and it has impacts on future financial flows of road administrator as well as economic aspects of transportation for the whole society. This paper describes analytical calculations and experimental measurements of surfacing materials, as well as accelerated pavement testing process needed for ascertainment of operational performance of a pavement construction during its life cycle. Finally, a case study encompassing the whole method is presented.